Análisis de perfil de textura, parámetros colorimétricos y microbiológicos en piña mínimamente procesada con recubrimientos comestibles - Buelvas-Caro, Saul David; Polo Corrales, Liliana; Hernández-Ramos, Elvis Judith (Ingeniería, 2022)
Context: The conservation of minimally processed fruits is a very important topic in the food industry due to the increased consumption of this type of food. This work studies the effects caused by edible coatings based on aloe vera and cassava starch on minimally processed pineapple. Method: Properties such as texture and color were evaluated, and microbial analysis was conducted after 12 days of storage at 4 °C. Four treatments (T1, T2, T3, and T4) were tested: Honey Gold pineapple with coating solutions of different aloe vera/starch concentrations (T1:75/25, T2:50/50, T3:25/75), and a control treatment (T4) consisting of the fruit without coating. Coating was carried out by immersing the fruit for 1 min. Results: The results indicated that the T2 treatment achieved the best texture, and that T4 showed a higher luminosity. The microbiological parameters remained within those established by the Colombian Technical Standard (NTC 4519) for minimally processed fruit during the 12 days of conservation. Conclusion: Edible coatings can maintain the texture and inhibit the growth of microorganisms in Honey Gold pineapple. However, fruit luminosity may be affected by the use of these edible coatings.